Uterine Sarcoma and Aromatase Inhibitors: Tom Baker Cancer Centre Experience and Review of the Literature. Issue 6 (1st July 2012) - Altman, Alon D.; Nelson, Gregg S.; Chu, Pamela; Nation, Jill; Ghatage, Prafull
Abstract : Objectives: Uterine sarcomas are a rare group of mesenchymal tumors with a poor prognosis and aggressive biology. Standard treatment involves surgical staging. The role of further adjuvant treatment is unclear. The goals of this study were to determine the response rates to treatment of patients with uterine sarcomas and to review the currently available literature on the use of aromatase inhibitors (AIs). Materials and Methods: We performed a retrospective analysis on all patients with uterine sarcoma treated with an AI between 2000 and 2010 at the Tom Baker Cancer Centre in Calgary, Alberta. Results: Four patients with endometrial stromal sarcoma and 3 patients with leiomyosarcoma received treatment with an AI. A literature search resulted in 10 case reports and 4 retrospective studies of patients with endometrial stromal sarcoma and 1 case report and 2 retrospective studies of patients with leiomyosarcoma. On the basis of the available literature, combined with the current findings, the overall response rate of endometrial stromal sarcoma to AIs is 67% (complete response of 7% and partial response of 60%), and the partial response rate of leiomyosarcoma to AIs is 11%, with no reported complete responses. Conclusions: Aromatase inhibitors are a well-tolerated class of medications that are effective in the treatment of endometrial stromal sarcomas. These medications may also have a role to help stabilize disease progression in the treatment of leiomyosarcoma. More large, prospective, multicentered trials will be needed to clarify this issue.